The role of circular shield in improving the thermal efficiency of domestic gas stove - Mingze Su; Yu Lin; Deqi Meng; Naiping Gao; Tong Zhu; Jiawei Chen; Dingrui Zhang; Zhonghua Li; Xiaowen Liu (Case Studies in Thermal Engineering)
Domestic gas stoves are widely used in the world as they are cheap and easy to use, therefore their thermal efficiency is one of the important factors affecting the great task of energy conservation and emission reduction. Installing a circular shield is the simplest and effective way to improve the thermal efficiency of domestic gas stove, but there is still no consensus on the role of installing a circular shield. In this paper, Computational fluid dynamics simulations were carried out to mimic the testing process of the thermal efficiency of domestic gas stove. Based on the simulation results, thermodynamic analysis was then conducted to determine the heat distribution in each heat transfer pathway. By means of the thermodynamic analysis, the main role of circular shield in improving the thermal efficiency of domestic gas stove was finally elucidated. The role can be expressed as: the circular shield establishes a radiation heat transfer pathway from the circular shield to the bottom wall of the pot, and through this pathway, the circular shield transfers heat absorbed from the flue gas to the bottom wall of the pot. The clarification of the above mechanism is helpful for the further optimization of circular shield.